Screening of microRNAs and target genes involved in Sclerotinia sclerotiorum (Lib.) infection in Brassica napus L. - Ling Xie; Hongju Jian; Haoxi Dai; Youhong Yang; Yiling Liu; Lijuan Wei; Min Tan; Jiana Li; Liezhao Liu (BMC Plant Biology, 2023)
Abstract Background Rapeseed (Brassica napus L.) is the third largest source of vegetable oil in the world, and Sclerotinia sclerotiorum (Lib.) is a major soil-borne fungal plant pathogen that infects more than 400 plant species, including B. napus. Sclerotinia stem rot caused an annual loss of 10 − 20% in rapeseed yield. Exploring the molecular mechanisms in response to S. sclerotiorum infection in B. napus is beneficial for breeding and cultivation of resistant varieties. To gain a better understanding of the mechanisms regarding B. napus tolerance to Sclerotinia stem rot, we employed a miRNAome sequencing approach and comprehensively investigated global miRNA expression profile among five relatively resistant lines and five susceptible lines of oilseed at 0, 24, and 48 h post-inoculation. Results In this study, a total of 40 known and 1105 novel miRNAs were differentially expressed after S. sclerotiorum infection, including miR156, miR6028, miR394, miR390, miR395, miR166, miR171, miR167, miR164, and miR172. Furthermore, 8,523 genes were predicted as targets for these differentially expressed miRNAs. These target genes were mainly associated with disease resistance (R) genes, signal transduction, transcription factors, and hormones. Constitutively expressing miR156b (OX156b) plants strengthened Arabidopsis resistance against S. sclerotiorum accompanied by smaller necrotic lesions, whereas blocking miR156 expression in Arabidopsis (MIM156) led to greater susceptibility to S. sclerotiorum disease, associated with extensive cell death of necrotic lesions. Conclusions This study reveals the distinct difference in miRNA profiling between the relatively resistant lines and susceptible lines of B. napus in response to S. sclerotiorum. The identified differentially expressed miRNAs related to sclerotinia stem rot resistance are involved in regulating resistance to S. sclerotiorum in rapeseed by targeting genes related to R genes, signal transduction, transcription factors, and hormones. miR156 positively modulates the resistance to S. sclerotiorum infection by restricting colonization of S. sclerotiorum mycelia. This study provides a broad view of miRNA expression changes after S. sclerotiorum infection in oilseed and is the first to elucidate the function and mechanism underlying the miR156 response to S. sclerotiorum infection in oilseed rape.